EFFECT OF SEVERITY AND ETIOLOGY OF CHRONIC KIDNEY DISEASE IN PATIENTS WITH HEART FAILURE WITH MILDLY REDUCED EJECTION FRACTION - RAMZAN, HS; RAWAT, A; MUSTAFA, G; SATTAR, S; SHAHEEN, A; ABDELGANI, AAA; LODHI, N; RAMZAN, Z (Biological and Clinical Sciences Research Journal, 2024)
This study explores the impact of chronic kidney disease (CKD) severity and etiology on patients with heart failure with mildly reduced ejection fraction (HFmrEF). Understanding these relationships is crucial for optimizing management strategies and improving patient outcomes. Methods: A cross-sectional study was conducted involving 550 patients diagnosed with HFmrEF. Patients were categorized based on CKD severity (stages 1 to 5) and etiology (diabetic nephropathy, hypertensive nephrosclerosis, glomerulonephritis, and others). Data on demographics, clinical characteristics, laboratory findings, and echocardiographic parameters were collected and analyzed. Results: Data were collected from 550 patients according to the study’s criteria. The mean age of the patients was 62.5 ± 10.8 years. Of 550, 320 (58.2%) were male, and 230 (41.8%) were female. According to the NYHA classification, 40 (7.3%) belong to Class I, 290 (52.7%) to Class II, 200 (36.4%) to Class III, and 20 (3.6%) to Class IV. Advanced CKD stage (OR 2.5, 95% CI 1.6-3.8), diabetic nephropathy (OR 1.8, 95% CI 1.1-3.0), and lower eGFR (OR 2.2, 95% CI 1.5-3.2) were all associated with increased risk of mortality and hospitalizations. Conclusions: It is concluded that the severity and etiology of chronic kidney disease significantly impact the outcomes of patients with heart failure with mildly reduced ejection fraction. Advanced CKD stages and diabetic nephropathy are associated with higher mortality rates and more frequent hospitalizations.